Using social network and dropbox in blended learning: an application to university education - Moreno, Justo de Jorge (Business, Management and Economics Engineering, 2012)
The main objective of this study is to analyze the use of the Social Networking and dropbox in blended learning by University students. We try identifying this method, over the student’s performance. The results show that the implementation of blended learning has a positive effect on in learning outcomes. The use of the Knowledge Management process has enabled captures a three-factor structure that reflected the five types of knowledge. The segmentation of the student sample analyzed using cluster technique, has established a clear typology of four groups. Students with higher levels of learning are related to the increased use of resources used and more proactive in blended learning.